The Digital Economy in the 21st Century - X. R. Bobobekova; M. X. Nurullayeva (International Journal on Human-Computing Studies, 2022)
Today, users are actively using Telegram bots to order groceries. Various online stores and electronic payment systems are also actively developing. This means that our citizens believe in the implementation of electronic transactions. Only to date, users are making small transactions that do not require large expenditures, and are less willing to increase the average purchase volume. The challenge now is to develop medium- and large-scale economic transactions and financial transactions through digital technologies.